Per se Performance and Variability in Dwarf Roselle Germplasm for Yield and Yield Attributing Traits - Saidaiah, P.; Pandravada, S. R.; Geetha, A. (International Journal of Bio-resource and Stress Management, 2021)
A research study was conducted with nine dwarf Roselle germplasm of H. sabdariffa var. sabdariffaat College of Horticulture, Sri Konda Laxman Telangana State Horticultural University, Hyderabad, Telangana State, India during first week, October, 2019 to 2nd week, January, 2020. The analysis of variance for yield and its contributing characters was found to be significant for all the characters. Based on mean performance, the Roselle accession SAS-14139-1 was the best performance for yield, number of fruits per plant and plant height. Seven accessions produced green calices with red tinging, which are having good demand in the market. Good amount of genetic variability was associated with the germplasm for majority of the characters. Significant differences (p<0.05) were observed for yield characters of the accessions. This is an indication that there is a store of genetic variability that can be exploited for the improvement of Roselle in India. There was also pronounced variation in yield and other morphological parameters, suggesting the possibility of evolving higher yield variants of Roselle through proper selection. High heritability was registered with plant height, number of branches per plant and fruit yield per plant. The present study identified agronomically better germplasm for yield exploitation coupled with high heritability characters for future varietal development and use as parents in further breeding programmes in Roselle, a future reliable vegetable crop.